2015
DOI: 10.1002/pssb.201552088
|View full text |Cite
|
Sign up to set email alerts
|

Determining doping efficiency and mobility from conductivity and Seebeck data of n-doped C60 layers

Abstract: In this work, we introduce models for deriving lower limits for the key parameters doping efficiency, charge carrier concentration, and charge carrier mobility from conductivity data of doped organic semiconductors. The models are applied to data of thin layers of Fullerene C60 n-doped by four different n-dopants. Combining these findings with thermoelectric Seebeck data, the energetic position of the transport level can be narrowed down and trends for the absolute values are derived.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Although the barrier value derived from the fitting of the case without the IL is larger than the maximum barrier, this difference is quite small and negligible. Carrier mobility fluctuation caused by IL penetration into the C 60 layer has been studied by Menke et al They investigated different ILs in different concentrations inside the C 60 layer and showed that there might be a reduction in carrier mobility with an increase in the dopant concentration in n -C 60 due to stronger scattering of carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Although the barrier value derived from the fitting of the case without the IL is larger than the maximum barrier, this difference is quite small and negligible. Carrier mobility fluctuation caused by IL penetration into the C 60 layer has been studied by Menke et al They investigated different ILs in different concentrations inside the C 60 layer and showed that there might be a reduction in carrier mobility with an increase in the dopant concentration in n -C 60 due to stronger scattering of carriers.…”
Section: Resultsmentioning
confidence: 99%
“…While an influence of the EA of tetracyanoquinodimethane (TCNQ)-based molecules was observed, a quantitative understanding of its influence is still missing. Similarly, in studies of n-doped C 60 , lower limits for the doping efficiency of various dopants were derived but without investigating the role of the energy level alignment between host and dopant . Here, we study a series of amorphous host materials with gradually increasing IE to uncover its influence on the host–dopant charge transfer efficiency, conductivity, and thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Modulating the charge carrier density by doping is considered a key strategy for optimizing the power factor and ZT value. [9][10][11][12] Recently, significant progress has been made in p-type organic thermoelectric studies with ZT = 0.42 by using p-type doped conjugated polymers. [13,14] Both efficient p-type and n-type TE materials are required for practical applications.…”
mentioning
confidence: 99%